Fra tugtemester til skolemester: Om forskelle mellem Luther og Grundtvig - Korsgaard, Ove (Grundtvig-studier, 2004)
Fra tugtemester til skolemester: Om forskelle mellem Luther og Grundtvig[From Castigator to Schoolmaster: On Differences between Luther and Grundtvig]By Ove Korsgaard Is Grundtvig’s thinking to be perceived as a genuine appropriation and continuation of Luther’s? Or is it rather to be perceived as a renegotiation of Luther’s thought? Regin Prenter, Christian Thodberg and Svend Bjerg maintain three different positions on the question of the relationship between Luther’s and Grundtvig’s theological thinking. With Prenter, a tight connection is tied. With Thodberg it is “both...and”. With Bjerg there is a marked distance between Luther’s and Grundtvig’s theology. In this article a more conceptual-historical viewpoint is adopted which demonstrates that they used the concepts “nation” and “folk” with differing significations.Luther does not use the word “nation” in its modem signification. According to Liah Greenfield: “he did not take the step that connected the separation from Rome to the definition of the polity as a people.The ‘ German nation’, for Luther, had none but the conciliar meaning of the princes and nobility of the Empire, and in this sense he used it in An den christlichen Adel deutscher Nation.” Grundtvig on the other hand used the word “nation” in its modem signification, that is to say, he made an inseparable connection between the concepts “nation” and “folk”. And he is surely the person who, in Denmark, has exercised the greatest influence in linking these two concepts.Before “nation” and “folk” became synonymous concepts, the word “folk” signified kinship and household. The societal whole was comprised, so to speak, of a certain number of households. Each household had as its supreme authority a householder who exercised English Summaries / danske resuméer power over his “folk”. The master tailor exercised power over the journeymen and apprentices who, together with children and other family members, belonged in the household. The combined households of a land were subordinate to a father of the land and belonged in his house, for example the Oldenburg House, the Habsburg House and so on. The supreme lord was the Lord God and all the houses within a society belonged in the final instance to his house. Individual freedom was no part of Luther’s political programme.His guardianship-society {formyndersamfund) was built not upon individual, responsible members of society but upon a fellowship between superiors and subordinates. The household constituted that social space within which a connection was forged between the individual and the Christian state. That Luther espoused political guardianship {formynderskab) as the best principle of governance is not remarkable. Everyone, more or less, did so at that time. The epochmaking and revolutionary thing about Luther was that he dispensed with the pope as religious guardian.But the sharp distinction which Luther drew between spiritual and secular governance is not, as is often alleged today, a distinction between State and Church but only between the State and “the Church Invisible”. In a continuation of Augustine, Luther in fact distinguished between two Churches, the invisible and the visible. The Church has both an outward, institutional and predominantly worldly side and an inward, invisible and predominantly spiritual side. As an incorporate member of the State one is obligated to be a member of the visible Church, that is to say the Church as an institution. Membership of the visible Church, however, grants no certainty of salvation. The visible Church cannot dispose over the relationship between the individual and God. Therefore membership of the visible Church is not enough to secure salvation. Faith is necessary. And faith is a personal and existential matter. With the doctrine of public polity, there is thus created a spiritual free-space. The formation of the individual’s morality and character, on the other hand, was placed under the aegis of secular government.Grundtvig grew up in a society whose world view was characterized by Luther’s thinking on calling and station. Lutherdom encompassed not only the obvious foundation in faith with respect to the Church but also the foundation in morality with respect to the State. However, Grundtvig himself was engaged in reassessing this foundation. After 1825 he began to distinguish himself with quite Luther-critical viewpoints, which is connected with the fact that he himself became one of the leading contemporary spokesmen for the new viewpoint that it was not the dispensations of Lutheranism but the dispensations of the folk which should comprise the moral foundation of State and school.The shift from Lutherdom to ‘folkdom’ meant that after 1825 Grundtvig again and again pointed to errors in Luther and his disciples. Thus he tackled three central dogmas in Lutherdom. The first was fundamentalism in respect of Scripture. The second was fundamentalism in respect of sin. The third was Lutherdom’s fundamentalism in respect of the State. For Grundtvig, the alliance which Constantine the Great established in 325 between State and Church was nothing less than a great lapse into sin in the history of the Church. And this lapse Luther had not tackled. The process of transformation from Christian principality to democratic nation-state demanded a clarification of the relationship between religion, State and polity. What form of connection should there be established between individual, State and religion in a democracy? Should Christianity, which was deeply integrated in the state-structure of the absolute monarchy, continue to comprise the foundation for the State’s educational polity? Grundtvig drew a clear boundary between citizenship and religion and, according to the ecclesiastical-political premises of his day, advocated religious freedom, freedom to preach, and dissolution of parochial ties. In simplified terms one can say that Luther’s horizon was a world divided into religions, and these were subdivided into nations, while Grundtvig’s horizon was a world divided into nations, and these could be subdivided into various religious societies.A conceptual-historical viewpoint reveals that Luther and Grundtvig not only used the concepts “nation” and “folk” with differing significations: theologically, they also thought differently upon crucial points. These differences can be put into perspective by looking at Luther’s categories “law and gospel”, “householder and household” and “parents and children” set off against Grundtvig’s use of “the knot” as metaphor.According to Grundtvig, Luther did not go far enough in his understanding of the relationship between law and gospel. He did not manage to untie the “tight knot” [Haardeknuden]. Instead of, like Luther, regarding the law as castigator, Grundtvig spoke of “ Moses as ‘schoolmaster’ for the whole world, who guides those desiring it to Jesus”. This shift in the view of the law - from castigator to schoolmaster - is a key to understanding Grundtvig’s thought.Grundtvig regarded the law as an “enlightenment of which one freely makes use according as one can and will”. Understood in Grundtvig’s English Summaries / danske resuméer terms, the law thus becomes a medium for folk-enlightenment. In other words, it is possible to untie the knot between the law and the gospel.The opening of the Gospel of John - In the beginning was the Logos - forms the basis of the whole of Grundtvig’s programme of enlightenment and exposition. Grundtvig distinguishes, however, between logos and dia-logos. Humankind does not have direct access to the logos of the great word, but must make do with the little word, the verity of which must be proved through dia-logos, that is, dialogue.For Grundtvig, “enlightenment” [Oplysning] is not an absolute, but a relative concept. The world cannot be overseen from a panoptic viewpoint, but necessarily has to be viewed with various eyes. The truth always emerges from out of the interplay between truths. Using a modem concept, one may say that for Gmndtvig enlightenment is a discursive concept, a concept open to argument. No one can boast of being in possession of the absolute tmth. We understand fragmentarily and in part. And such a process of understanding demands, according to Grundtvig, faith.[Editorial note: Danish tugtemester, as used in this context to refer to the Law, is not readily translatable into English. A tugtemester is one who enforces discipline by chastisement and castigation, whether a gaoler, a slavemaster, a disciplinarian pedagogue addicted to flogging or a rigorous moral tutor.]